2016
DOI: 10.1021/acs.est.6b02406
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical Controls of Uranium Bioavailability from the Dissolved Phase in Natural Freshwaters

Abstract: To gain insights into the risks associated with uranium (U) mining and processing, we investigated the biogeochemical controls of U bioavailability in the model freshwater species Lymnaea stagnalis (Gastropoda). Bioavailability of dissolved U(VI) was characterized in controlled laboratory experiments over a range of water hardness, pH, and in the presence of complexing ligands in the form of dissolved natural organic matter (DOM). Results show that dissolved U is bioavailable under all the geochemical conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 36 publications
(68 reference statements)
4
26
2
Order By: Relevance
“…Contrary to the conventional wisdom that mono-nuclear complexes are more bioavailable (Bernhard et al, 1998;Croteau et al, 2016;Drobot et al, 2015;Du et al, 2011;Guillauont et al, 2003;Jones et al, 2015;Kulkarni et al, 2016), we found that all of the mono-nuclear, and poly-nuclear species of U(VI) were about equally bioavailable. This means that pH should not affect U(VI) respiration as long as pH itself is not inhibitory.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Contrary to the conventional wisdom that mono-nuclear complexes are more bioavailable (Bernhard et al, 1998;Croteau et al, 2016;Drobot et al, 2015;Du et al, 2011;Guillauont et al, 2003;Jones et al, 2015;Kulkarni et al, 2016), we found that all of the mono-nuclear, and poly-nuclear species of U(VI) were about equally bioavailable. This means that pH should not affect U(VI) respiration as long as pH itself is not inhibitory.…”
Section: Discussioncontrasting
confidence: 99%
“…Cytochrome c3 has a mid-point redox potential near −300 mV versus SHE (standard hydrogen electrode) at 25°C (Niki et al, 1984), while the U(VI)-U(IV) couple has a mid-point potential of +334 mV versus SHE of dissolved inorganic carbon (DIC) and with a wide range of pH is of paramount importance for understanding microbial reduction of U(VI), since different U(VI) species could have different susceptibilities of being reduced based on their bioavailability. A decrease in U(VI) reduction rate with increasing DIC concentration, along with sensitivity towards pH, has been well documented in the literature (Belli et al, 2015;Bernhard, Geipel, Brendler, & Nitsche, 1998;Brooks et al, 2003;Croteau, Fuller, Cain, Campbell, & Aiken, 2016;Drobot et al, 2015;Guillauont et al, 2003;Jones et al, 2015;Sheng & Fein, 2014;Ulrich et al, 2011).…”
Section: Electron Flow and Speciationmentioning
confidence: 71%
See 3 more Smart Citations